An efficient conversion of waste feather keratin into ecofriendly bioplastic film - Sharma, Swati; Kumar, Ashok; Chua, Gek Kee; Kamyab, Hesam; Syed Mohd Saufi, Tuan Chik (Springer International Publishing, 2018)
Feathers biomass from poultry industry is considered as an important waste product, which creates serious environmental problems. In this study, keratin was extracted from waste chicken feathers using sodium sulfide as a reducing agent under optimized conditions. The extracted keratin particles were used to develop a bioploymeric film by adding microcrystalline cellulose as nano-additive agent. The calculated yield of 80.2% was obtained for keratin from feathers dry weight 25 g (w/w). The extracted keratin was characterized using Fourier transform infrared spectroscopy, scanning electron microscopy (SEM), thermogravimetric analysis, differential scanning calorimetry, wide-angle X-ray diffraction. The physiochemical characteristics of the feathers were compared with the keratin powder. The regenerated keratin particles preserved their chemical composition, thermal strength and stability after chemical extraction. The extracted keratin particles showed 10–20-µm spongy porous microparticles in SEM analysis. The keratin powder was used to synthesize a bioplastic film using glycerol (3.5%) and microcrystalline cellulose (0.2%) in NaOH for 48 h at 60 °C. The calculated thickness of bioplastic film was 1.12 × 10−4 mm with tensile strength of 3.62 ± 0.6 MPa. The Young’s modulus and break elongation for synthesized bioplastic film were 1.52 ± 0.34 MPa and 15.8 ± 2.2%, respectively. The feather and keratin showed maximum similarity index of 64.74% (l-alanyl, l-alanyl, l-alanine, p-nitroanilide) and 64.32% with d-pantethine, respectively, using OMNIC Specta software. Overall, the study presented a highly efficient method to convert the waste feather biomass into a bioplastic film which can be used in biopolymer, biomedical and pharmaceutical industries.